2017
DOI: 10.11622/smedj.2016147
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and anatomical distribution of hand tumours: a Singapore study

Abstract: RESULTS Overall, the most common tumours excised from the hand were ganglions (n = 66/116, 56.9%) and giant cell tumours of the tendon sheath (GCTTSs; n = 11/116, 9.5%). However, distal to the MCPJs, GCTTSs (n = 11/39, 28.2%) were more common than ganglions (n = 7/39, 17.9%). Most of the ganglions (n = 59/66, 89.4%) arose from between the CMCJs and RCJ.CONCLUSION Most hand tumours were benign. Ganglions were the most common tumours between the CMCJs and RCJ, while GCTTSs were the most common tumours distal to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…Al-Qattan (10) however, found that the index finger and middle fingers were the most involved in GCTs in a Saudi Arabian study. We found that there was a statistically significant difference between the sides, with more lesions found on the right side, a finding also reported by Tang et al (13) in a study in Singapore. They found that 9/11(81%) cases of GCTs occurred on the right side of the hand, although this was not statistically tested.…”
Section: Discussionsupporting
confidence: 90%
“…Al-Qattan (10) however, found that the index finger and middle fingers were the most involved in GCTs in a Saudi Arabian study. We found that there was a statistically significant difference between the sides, with more lesions found on the right side, a finding also reported by Tang et al (13) in a study in Singapore. They found that 9/11(81%) cases of GCTs occurred on the right side of the hand, although this was not statistically tested.…”
Section: Discussionsupporting
confidence: 90%
“…GCs are the most common tumors of the hand. Although they rarely deteriorate, [ 16 ] they often cause pain, leading to significant motor dysfunction in the affected joint, which in turn reduces the patient's quality of life. Because the pathogenesis is not clear, according to the existing treatment principles, drug treatment is mainly non-steroidal anti-inflammatory drugs injection, non-drug treatment is mainly puncture aspiration, and surgical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…2 They are often asymptomatic but may cause sufficient symptoms for definitive surgical excision. Not surprisingly, ganglions are also the most common tumors to be excised in the hand according to Tang et al 1 The use of cadavers in surgical training is very popular. Trainees and trainers hold them in high regard as they feel it helps to improve their operative skills.…”
Section: Introductionmentioning
confidence: 99%
“…Ganglions are one of the commonest tumors of the hand, accounting for approximately 60% of all hand tumors. 1 They can be found on the dorsum of the wrist over 70% of the time. 2 They are often asymptomatic but may cause sufficient symptoms for definitive surgical excision.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation